Cognitive Impairment in Non-critical, Mild-to-Moderate COVID-19 Survivors - Henneghan, Ashley M.; Lewis, Kimberly A.; Gill, Eliana; Kesler, Shelli R. (Frontiers in psychology, 2022)
Previous studies of post-acute COVID-19 syndrome have focused on critical cases with severe disease. However, most cases are mild to moderate in disease severity. We aimed to examine cognitive outcomes in cases of non-critical, mild-to-moderate COVID-19. Design, Setting, and Participants: In this cross-sectional study, we enrolled 72 adults aged 22 to 65 years in Central Texas who had non-critical, mild-to-moderate COVID-19 infection between 13 January 2021 and 20 April 2021. We remotely administered cognitive-behavioral testing to determine the frequency of cognitive impairment and examine demographic, clinical, and psychosocial contributors to impairment. The frequency of objective cognitive impairment was 40%. The largest number of participants (24%) showed impairment on a measure of executive functioning. Attention and processing speed was more impaired in males ( = 1.5, 95%CI = 0.23-2.9). Males endorsed lower adherence to social distancing guidelines ( = 590, = 0.01), which was in turn associated with cognitive impairment across participants ( = -0.30, = 0.01). Younger age was correlated with impairment ( = -0.26, = 0.03) but was also associated with racial/ethnic minority status ( = -0.31, = 0.01) and increased psychological symptoms ( < 0.04). Greater number of COVID-19 symptoms was correlated with lower subjective cognitive function ( = -0.38, = 0.001) as well as psychosocial function ( > 0.24, < 0.05). Moderate COVID-19 severity was associated with attention/processing speed impairment ( = 0.27, = 0.03), increased pain ( = 0.31, = 0.01), and higher number of COVID-19 symptoms ( = 0.32, = 0.01). Mild or moderate COVID-19 infection may be associated with cognitive impairments, especially in the domain of executive functioning. A subgroup of younger individuals may be more vulnerable to cognitive and psychosocial effects of COVID-19. Question: How frequent is cognitive impairment among non-critical, mild-to-moderate COVID-19 survivors? In this cross-sectional study of 72 adults, 40% demonstrated cognitive impairment, particularly in executive function. Neurologic sequelae, such as cognitive impairment, may be common following COVID-19 infection.